PROBLEMATIKA LANSIA RENTAN YANG BEKERJA DI SEKTOR INFORMAL - Fujiyama Zilzia Putri; Afnibar Afnibar; Jemkhairil Jemkhairil; Fitra Yanti (TATHWIR: Jurnal Pengembangan Masyarakat Islam, 2023)
The changes faced by the elderly have the potential to become a source of pressure in life from various aspects of life. So that the elderly become vulnerable people who continue to fight for life until the end. The elderly have continued to carry out various professions in the informal sector to be able to stay strong and survive without depending on others. The aim of the research is to find out the problems of the elderly from personal, socio-economic and spiritual aspects. Research using qualitative methods is descriptive. The research location was in the Piai Tangah Village, RT 01 RW 03. The research subjects were elderly people who worked in the informal sector, using the accidental sampling technique, as many as 7 people were obtained. Data collection techniques are observation and interviews. The findings of the study are, the elderly say decreased physical ability affects the activities of the elderly at work. The elderly withdraw from the environment because they no longer have peers, feel alienated from the environment, and choose to work so that the elderly are busy with their work activities. Still working makes the elderly feel empowered in society even though it sometimes creates feelings of inferiority in society, they feel not cared for by their family, they are lonely, they feel alienated from society but they are elderly. Working interferes with the elderly's worship time, such as: not being able to pray five times a day at the mosque, not being able to attend religious lectures and recitations.